EU structural support and its impact on Lithuania's progress - Tamošiūnienė, Rima; Šidlauskas, Skirmantas; Trumpaitė, Ingrida (Journal of Business Economics and Management, 2007)
During the last years the changes of social ‐ economic situation have been fast, however, according to individual macroeconomic indexes Lithuania is still significantly below the average of EU countries. To decrease these discrepancies the EU grants the structural support, the use of which is anticipated to establish strong and competitive economy, to train qualified labour force and stimulate social and economic cohesion. The efficient and expedient use of the EU support would enable Lithuania to implement the national Lisbon strategy programme and contribute to the implementation of the very Lisbon strategy guidelines. However, the investigations showed that the use of the support is not sufficient enough to secure the efficient progress of the country. The article analyses the aspects of the EU regional policy financing and the expected results of implementing the Lisbon strategy actions; it analyses economic, social, environmental, and other indexes of the economies of Lithuania and EU countries and assesses the result of the country's progress in implementing the Lisbon strategy. The research on the expedience of using the EU structural support and its impact on the country's progress was carried out. The research made on the use of the EU support and its impact on the country's progress suggests that about two thirds of the measures correspond to the national programme for implementing the Lisbon strategy but only few indicators have a complex influence on the progress indexes. Therefore, while preparing the programmes of the EU support use for 2007–2013 and coordinating them with the EU Commission a better harmonization of this support use measures with the national programme for implementing the Lisbon strategy is necessary, and the measures have to be implemented in a complex manner, as well as the horizontal compatibility of the measures has to be maintained.First Published Online: 14 Oct 2010